Advanced computed tomographic anatomical and morphometric plaque analysis for prediction of fractional flow reserve in intermediate coronary lesions - Opolski, Maksymilian P.; Kepka, Cezary; Achenbach, Stephan; Pregowski, Jerzy; Kruk, Mariusz; Staruch, Adam D.; Kadziela, Jacek; Ruzyllo, Witold; Witkowski, Adam (European Journal of Radiology, 2014)
To determine the application of advanced coronary computed tomography angiography (CCTA) plaque analysis for predicting invasive fractional flow reserve (FFR) in intermediate coronary lesions.Sixty-one patients with 71 single intermediate coronary lesions (>= 50-80% stenosis) on CCTA prospectively underwent coronary angiography and FFR. Advanced anatomical and morphometric plaque analysis was performed based on CCTA data set to determine optimal criteria for significant flow impairment. A significant stenosis was defined as FFR <= 0.80.FFR averaged 0.85 ± 0.09, and 19 lesions (27%) were functionally significant. FFR correlated with minimum lumen area (MLA) (r=0.456, p<0.001), minimum lumen diameter (MLD) (r=0.326, p=0.006), reference lumen diameter (RLD) (r=0.245, p=0.039), plaque burden (r=-0.313, p=0.008), lumen area stenosis (r=-0.305, p=0.01), lesion length (r=-0.692, p<0.001), and plaque volume (r=-0.668, p<0.001). There was no relationship between FFR and CCTA morphometric plaque parameters. By multivariate analysis the independent predictors of FFR were lesion length (beta=-0.581, p<0.001), MLA (beta=0.360, p=0.041), and RLD (beta=-0.255, p=0.036). The optimal cutoffs for lesion length, MLA, MLD, RLD, and lumen area stenosis were >18.5mm, <= 3.0mm(2), <= 2.1mm, <= 3.2mm, and >69%, respectively (max. sensitivity: 100% for MLA, max. specificity: 79% for lumen area stenosis).CCTA predictors for FFR support the mathematical relationship between stenosis pressure drop and coronary flow. CCTA could prove to be a useful rule-out test for significant hemodynamic effects of intermediate coronary stenoses.
EVALuna2:11882